Youth and wellbeing: experiencing bereavement and ill health in marginalised young people's transitions. Issue 1 (28th June 2012) - MacDonald, Robert; Shildrick, Tracy
Abstract: Research that explores youth transitions, health, bereavement and wellbeing is rare. Rarer still is research that does this on the basis of long‐term, longitudinal, qualitative research with socioeconomically disadvantaged young people. This article draws upon biographical interviews undertaken with 186 young adults in some of England's poorest neighbourhoods (in Teesside, North East England) to examine how experiences of health, wellbeing and bereavement interact with processes of youth transition and social exclusion. Depression was the most widespread health problem arising from the multiple pressures and hardships encountered in contexts of severe socioeconomic deprivation. Unpredictable 'critical moments' (for example, of bereavement) were common and had unpredictable consequences for youth transitions. It is argued that research of this sort, particularly with a close, qualitative and biographical focus on critical moments, has value for research about youth, health and wellbeing that seeks to better understand how spatially concentrated, class‐based inequalities are lived by young people and play out in their lives.